Legal arrangements on post divorce child custodial - Erwin Dwi Kurnia,; Fika Rifatus Fadiana,; Muhammad Abid Rusydi,; Sultoni Fikri,; Tomy Michael,; Irmasanthi Danadharta,; Muchamad Rizqi, (Technium Social Sciences Journal, 2022)
One of the most important events in human life is marriage. Humans as social beings cannot live alone, therefore to fulfill their biological needs or want to obtain offspring, humans must legally marry according to the laws in force in Indonesia. Regarding marriage in the state of Indonesia as regulated in the applicable laws and regulations. Based on Law Number 16 of 2019 concerning amendments to Law Number 1 of 1974 article 2 it is said that "Marriage is legal if it is carried out according to the laws of each religion." Disputes over child custody is one of the consequences of the breakup of marriage or divorce between husband and wife. When the divorce leaves a child, according to Burgerlijk Wetboek, children who are not yet adults who are not under parental control must be submitted under guardianship. Based on the research that has been done in Bedalawak Village, in this study the author uses a normative juridical research method. Children are a mandate and gift from God Almighty which in the child is inherent in the dignity and worth as a whole human being. Children are buds, potentials, and the younger generation who will succeed the ideals of the nation's struggle, have a strategic role and have special characteristics and characteristics that ensure the continuity of the existence of the nation and state in the future. Families, parents, government, and society must participate in the care or protection of children. Marriage is a bond that binds two human beings because humans are actually created in pairs. Humans are social creatures, where humans were created by God who cannot live alone and always need the help of others. All families always crave a harmonious family and there is no word of divorce after marriage. One of the noble deeds and should not be damaged and divided by trivial things is marriage.